Kids' Environment and Health Cohort: Database Protocol - Akaraci, Selin; Macfarlane, Alison; Rammah, Amal; Courtin, Emilie; Lewis, Esther; Miller, Faith; Powell-Bavester, Jason; Mitchell, Jessica; Cruz, Joana; Lilliman, Matthew; Shoari, Niloofar; Hajna, Samantha; et al. (International Journal of Population Data Science, 2025)
Introduction Environmental exposures are known to affect the health and well-being of populations throughout the life course. Children are particularly susceptible to environmental impacts on educational and health outcomes as they spend more time in their local environments compared to adults. In England, no national, longitudinal dataset linking information about the physical and social environment in and around homes and schools to children's health and education outcomes currently exists. This limits our understanding of how environments might impact the health and well-being of children as they grow up. Objective To establish the Kids' Environment and Health Cohort, a research-ready, de-identified and annually updated national birth cohort of all children born in England from 2006 onwards. Methods The Kids' Environment and Health Cohort will link birth and mortality records, health and educational attainment datasets, to maternal health (up to 12 months prior to their child's birth), and environmental data for all children born in England from 2006 -- approximately 11 million children at first build. A subset of children born between 2010 and 2012, and between 2020 and 2022 will be linked to their mothers' 2011 or 2021 Census records, respectively. The cohort database will be held in, and accessed via, a trusted research environment (TRE) at the Office for National Statistics (ONS). All geographical identifiers in the cohort, allowing for linkage to further environmental data, will be securely held by the ONS, separately to the main cohort, and will be encrypted before being shared with researchers. Conclusion The Kids' Environment and Health Cohort will, for the first time, link administrative health and education data to longitudinal environmental exposures for children at national level in England. It will serve as a data resource to support research about the health and well-being of children via improved home and school environments.